Economic growth and electricity consumption: Auto regressive distributed lag analysis - Bildirici, Melike E.; Bakirtas, Tahsin; Kayikci, Fazil (UNIV CAPE TOWN, ENERGY RES CENTRE, 2012)
Knowledge of the direction of causality between electricity consumption and economic growth is of primary importance if appropriate energy policies and energy conservation measures are to be devised. This study estimates the causality relationship between electricity consumption and economic growth in per capita and aggregate levels. The study uses the price and income elasticities of total electricity demand and industrial demand by using the auto regressive distributed lag (ARDL) method for some developed and developing countries, including the US, UK, Canada, Japan, China, India, Brazil, Italy, France, Turkey and South Africa. There is evidence to support the growth hypothesis for the US, China, Canada and Brazil. There is evidence to support the conservation hypothesis for India, Turkey, South Africa, Japan, UK, France and Italy.
Keywords: growth; development; electricity consumption; ARDL; ENERGY-CONSUMPTION; RESIDENTIAL DEMAND; COINTEGRATION ANALYSIS; EMPIRICAL-ANALYSIS; INDUSTRIAL DEMAND; OUTPUT; CHINA; TIME; GDP; ELASTICITIES; Energy & Fuels